An Analysis of Interlingual and Intralingual Errors in Using Simple Past Tense in Recount Text Committed by the Eighth Grade Students of SMP Negeri 1 Banjar in the Academic Year 2013-2014 - ., Ni Putu Lisa Pebrianti; ., Prof. Dr. Putu Kerti Nitiasih, MA; ., Putu Eka Dambayana S., S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian in bertujuan untuk mengidentifikasi kesalahan interlingual dan intralingual dalam penggunaan simple past tense pada teks recount. Penelitian ini termasuk dalam descriptive qualitative research. Subjek penelitian ini adalah seluruh siswa kelas 8 SMP N 1 Banjar. Data yang diperoleh bersumber dari beberapa instrumen, yaitu tes menulis dan interview. Hasil penelitian menunjukkan bahwa ada 749 kesalahan yang dilakukan siswa dalam tulisannya. Jenis error yang paling banyak muncul pada tulisan siswa adalah kesalahan intralingual dengan frekuensi kemunculan sebesar 445 atau 59.42 %. Sedangkan kesalahan interlingual sebesar 304 atau 40.58 %. Penyebab dari kesalahan siswa adalah kurangnya pengalaman siswa terhadap bahasa target dalam proses penguasaan bahasa inggris dan siswa tidak terbiasa dengan struktur kalimat dalam bahasa inggris, sehingga siswa memilih untuk menggunakan bahasa pertama dalam menyusun kalimat.Kata Kunci : kesalahan interlingual, kesalahan intralingual, simple past tense, teks recount. This study intended to identify the interlingual and intralingual errors in using simple past tense in recount text. This study was a descriptive qualitative research. The eighth grade students of SMP N 1 Banjar were subjects of this study. The data were collected by using several instruments, namely: writing task and interview guide. The results of the study showed that there were total 749 errors committed by the students in their writing. The type of error that most frequently occurred in students’ writings was intralingual error with 445 occurrences or 59.42 %. Meanwhile interlingual error was 304 occurrences or 40.58 %. The causes of student’ errors were mostly their limited experience about the target language as they were in the process of mastering English and they were not familiar with sentence structures of English so that they preferred to use their mother’ tongue in constructing the sentences.keyword : interlingual error, intralingual error, simple past tense, recount text.